Non-conformal behavior of holographic entanglement measures - M. Ali-Akbari; M. Asadi; B. Amrahi (Journal of High Energy Physics, 2022)
Abstract We evaluate the holographic entanglement entropy, HEE, holographic mutual information, HMI, and holographic entanglement of purification, EoP, in a non-conformal model at zero and finite temperature. In order to find the analytical results we consider some specific regimes of the parameter space. We find that the non-conformal effects decrease the redefined HEE and increase the redefined HMI and EoP in the all studied regimes. On the other side, the temperature effects increase (decrease) the redefined HEE (HMI) in the all studied regimes while it has no definite effect on the redefined EoP. Finally, from the information point of view, we find that in the vicinity of the phase transition the zero temperature state is more favorable than the finite temperature one.